Crocodile Skin‐Inspired Protective Composite Textiles with Pattern‐Controllable Soft‐Rigid Unified Structures. (10th January 2023) - Mao, Lizhou; Zhou, Mengjuan; Yao, Lu; Yu, Hang; Yan, Xuefeng; Shen, Yue; Chen, Wenshuai; Ma, Pibo; Ma, Yan; Zhang, Songlin; Tan, Swee Ching
Abstract: Functional textiles with desirable protective properties (i.e., high cut‐, stab‐, and abrasion resistance) and wearability (i.e., excellent flexibility and permeability) remain unmet goals for personal protective equipment. Herein, inspired by crocodile skin, a unique and soft‐rigid unified structure (SRUS) is reported by integrating rigid protective blocks onto a soft textile substrate while obtaining a high cut‐, stab‐, and abrasion‐resistant composite textile that is flexible, waterproof, and breathable. Rigid blocks, consisting of epoxy resin reinforced by inorganic powders, strongly adhere to the soft textile surface with small intervals between each other via a pattern‐controllable integrated molding (PCIM) approach. Consequently, the SRUS design guarantees superior protective performance through rigid protective blocks and satisfactory flexibility and permeability via soft textiles and intervals. The SRUS textile achieves excellent cut‐resistance (58 N), the highest grades of stab‐ (38 N) and abrasion‐resistance (600 r mg −1 ), and good flexibility (65 mN cm) and permeability (60 mm s −1 ) values, indicating a distinct combination of desirable protective and wearable performance. The proposed SRUS protective textiles, incorporating the PCIM approach, offer a novel strategy for manufacturing functional soft composite textiles that combine high protective performance and good wearability, opening up a new avenue for the development of personal protective equipment. Abstract : The soft‐rigid connection structure (integrated rigid protective block array onto a soft textile substrate) inspired by crocodile skin enables excellent cut resistance (58 N), outstanding stab resistance (38 N), and superior abrasion resistance (600 r mg −1 ) to the functional composite textiles, which also demonstrates good flexibility (65 mN cm) and permeability (60 mm s −1 ).